Pandangan Guru Dan Siswa Terhadap Nilai-Nilai Karakter Melalui Pembelajaran Fiqih Di MtsN 2 Kota Cilegon - Luthfi, HM; Hasbullah, Hasbullah; Marantika, Amelia; Azizah, Umamah (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The purpose of this descriptive qualitative research is to determine the views of teachers and students on character values ​​through Islamic jurisprudence learning at MTsN 2 Cilegon City. The focus is on the learning activities of Islamic jurisprudence teachers and school programs related to worship by interviewing several teachers, the principal, and students. Teachers and students have a very positive view of Islamic jurisprudence learning at MTsN 2 Cilegon City. In shaping student character, it is marked by students' very polite behavior towards teachers and friends. This success is certainly due to the existence of several programs carried out by Islamic jurisprudence teachers in providing lessons to students. However, from this success, several driving and inhibiting factors were found.